2015
DOI: 10.3390/v7052358
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of 15 Human Coronaviruses OC43 (HCoV-OC43s) Circulating in France from 2001 to 2013 Reveals a High Intra-Specific Diversity with New Recombinant Genotypes

Abstract: Human coronavirus OC43 (HCoV-OC43) is one of five currently circulating human coronaviruses responsible for respiratory infections. Like all coronaviruses, it is characterized by its genome’s high plasticity. The objectives of the current study were to detect genetically distinct genotypes and eventually recombinant genotypes in samples collected in Lower Normandy between 2001 and 2013. To this end, we sequenced complete nsp12, S, and N genes of 15 molecular isolates of HCoV-OC43 from clinical samples and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 54 publications
1
77
0
3
Order By: Relevance
“…Phylogenetic trees based on the whole genome and S gene HCoV−OC43 show that genotypes B, G, E and F currently circulate among French patients, in agreement with other report [29]. Even if HCoV−OC43 was previously detected among patients with haematology malignancy, the involvement of HCoV−OC43 genotypes in this type of infection was rarely investigated [38][39][40].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Phylogenetic trees based on the whole genome and S gene HCoV−OC43 show that genotypes B, G, E and F currently circulate among French patients, in agreement with other report [29]. Even if HCoV−OC43 was previously detected among patients with haematology malignancy, the involvement of HCoV−OC43 genotypes in this type of infection was rarely investigated [38][39][40].…”
Section: Discussionsupporting
confidence: 88%
“…Strains described here represent probably a part of strains currently circulating among European people. However, our data show that both kinds of HCoV−OC43 strains circulate among patients included in the study: those belonging to the genotype G closely related to Asian strains and other belonging to the genotype F more related to other European strains previously described [25,26,28,29,41]. Amino acid substitution analyses showed that some substitutions especially in the S protein could be specific of strains circulating in European population but the number of strains analyzed here and the number of sequences obtained from European isolates of HCoV−OC43 are too small and further studies will be needed to confirm our data.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Genotype E, identified in 2014, emerged by recombination amongst the genotype B, C, and D viruses with different breakpoints in the genes compared to the generation of genotype D [76] (Figure 4). A study in France, between 2001 and 2013, demonstrated that OC43 strains have more recombination patterns in Lower Normandy, and circulating OC43 viruses have a high genetic diversity [17].…”
Section: Mutation and Genetic Recombination In Coronavirusesmentioning
confidence: 99%
“…Currently, six different CoV strains are known to infect humans. These include: HCoV-229E (229E), HCoV-OC43 (OC43), severe acute respiratory syndrome coronavirus (SARS-CoV), HCoV-NL63 (NL63), HCoV-HKU1 (HKU1), and Middle East respiratory syndrome coronavirus (MERS-CoV) [17]. 229E and OC43 are the prototype viruses from the two main HCoV lineages (Alpha and Beta, respectively) that cause 15-29% of all common colds, and are the best characterized [18].…”
mentioning
confidence: 99%